2016
DOI: 10.1371/journal.pgen.1006247
|View full text |Cite
|
Sign up to set email alerts
|

A let-7-to-miR-125 MicroRNA Switch Regulates Neuronal Integrity and Lifespan in Drosophila

Abstract: Messenger RNAs (mRNAs) often contain binding sites for multiple, different microRNAs (miRNAs). However, the biological significance of this feature is unclear, since such co-targeting miRNAs could function coordinately, independently, or redundantly with one another. Here, we show that two co-transcribed Drosophila miRNAs, let-7 and miR-125, non-redundantly regulate a common target, the transcription factor Chronologically Inappropriate Morphogenesis (Chinmo). We first characterize novel adult phenotypes assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 86 publications
(122 reference statements)
4
80
1
4
Order By: Relevance
“…Many of these miRNAs also exhibited overlapping cellular functions, contributing to processes such as tumorigenesis [23][24][25][26][27][28][29][30], differentiation [31][32][33], proliferation [34][35][36][37][38], apoptosis [39][40][41][42], and cell cycle regulation [34,43,44]. A subset of the miRNAs was associated with nervous system-specific processes, such as differentiation [45][46][47][48][49], lifespan [50], neurite guidance [51][52][53], or synaptogenesis [54][55][56]. We were specifically interested in miRNAs known to contribute to neuronal differentiation and/or axonal guidance, processes that are known to be regulated by RA [10,57].…”
Section: Identification Of Mirnas That Were Differentially Regulated mentioning
confidence: 99%
“…Many of these miRNAs also exhibited overlapping cellular functions, contributing to processes such as tumorigenesis [23][24][25][26][27][28][29][30], differentiation [31][32][33], proliferation [34][35][36][37][38], apoptosis [39][40][41][42], and cell cycle regulation [34,43,44]. A subset of the miRNAs was associated with nervous system-specific processes, such as differentiation [45][46][47][48][49], lifespan [50], neurite guidance [51][52][53], or synaptogenesis [54][55][56]. We were specifically interested in miRNAs known to contribute to neuronal differentiation and/or axonal guidance, processes that are known to be regulated by RA [10,57].…”
Section: Identification Of Mirnas That Were Differentially Regulated mentioning
confidence: 99%
“…The 'drift-draft' model is based on the observation that a majority of microRNA clusters are formed during evolution by the random emergence of novel microRNAs near existing microRNA genes in the genome. Although functional co-adaptation may explain some observed patterns in specific microRNA clusters (see for instance (Chawla et al 2016)), the evidence presented so far does not indicate that this is a widespread phenomenon. Here I show that the results presented by Wang et al (2016) do not support the conclusion that clustered microRNAs target overlapping sets of genes more than expected by chance, and therefore, there is no evidence of functional co-adaptation of clustered microRNAs.…”
Section: Introductionmentioning
confidence: 84%
“…It is suggested that let-7 forms a regulatory cycle in the circadian clock being activated indirectly by CLK/CYC through the ecdysteroid pathway and negatively regulates the expression of cwo . Further, let-7 , miR-8 , and miR-34 are essential players in preventing neurodegeneration process and aging in D. melanogaster (Liu et al 2012a, b;Chawla et al 2016). miR-92a has an oscillatory expression in circadian neurons of fruit flies and modulates the neuronal excitability through regulation of sirt2 (Chen and Rosbash 2016).…”
Section: Discussionmentioning
confidence: 99%